Effectiveness of a Project Based Learning Model Integrated With Sasambo Local Wisdom to Enhance Students' Scientific Attitudes - Rahman*, Nanang; Liswijaya, Liswijaya; Hendratmoko, Ahmad Fauzi; Nagy, Emese K.; Mashwani, Hazrat Usman (Jurnal IPA & Pembelajaran IPA, 2025)
The primary issue in higher education is the low level of scientific attitudes among students, which include curiosity, open-mindedness, and environmental sensitivity. One approach to addressing this problem is through the project based learning (PjBL) model integrated with local wisdom. This study aims to measure the effectiveness of the PjBL integrated sasambo local wisdom model, which incorporates values such as cooperation, respect for nature, and social harmony, in enhancing students' scientific attitudes. The study employed a quasi-experimental design with a one-group pretest-posttest approach. The research subjects consisted of 70 students from Muhammadiyah Mataram University and Hamzanwadi University. Data were collected using a scientific attitude questionnaire with five indicators: curious attitude, respect for facts, an open-minded attitude, perseverance, and sensitivity toward the environment. The data were analyzed using normalized N-gain to measure the improvement in scientific attitudes and inferential statistical tests to assess the significance of the results. The findings reveal that the sasambo integrated PjBL model effectively improves students' scientific attitudes. The average N-gain was categorized as high (0.81 and 0.83) at both universities. Among the indicators, sensitivity toward the environment showed the greatest improvement, while respect for facts showed moderate improvement. Statistical tests indicated a significant difference between pretest and posttest scores, with consistent results across both universities. In conclusion, the the PjBL integrated sasambo local wisdom model significantly and consistently enhances students' scientific attitudes. This model holds potential as a culturally relevant innovative strategy for improving the quality of science education and fostering students' character development